TOURISTS’ INTENTION TO VISIT POST-DISASTER DESTINATION - Alverina Agusta Sitio (Universitas Mercu Buana, 2022)
Lombok was hit by an earthquake of 7.0 magnitude on the mid of 2017. As a tourist destination, such disaster had a negative impact where its inbound tourist decreased to almost 75% on the following year. However, there is a possibility that Lombok may shift its destination image into a post-disaster destination. Such concept has been documented on tourism literatures, where scholars investigate the peculiarities of tourists’ travel motivation to the post-disaster destinations. However, there is a lack of investigation regarding the negative tourists’ motivations in the context of post-disaster destinations. Thus, this study aims to fill this gap by investigating the relationships of perceived risks and travel constraints toward tourists’ intention to visit. Additionally, using the push-pull motivation theory, this study also investigates the mediating effect of destination image.